The complete mitochondrial genome of Steppe Whiskered Bat (Myotis aurascens; Kuzyakin, 1935) and phylogenetic analysis. Issue 4 (3rd April 2022) - Yang, Xiufeng; Wang, Qi; Zhang, Lei; Bao, Saru; Zhao, Shihu; Dou, Huashan; Zhang, Honghai
Abstract: In this study, the complete mitochondrial genome of Steppe Whiskered Bat was sequenced for the first time using muscular tissue. The whole mitochondrial genome was 16, 771 bp in length, consisting of two ribosomal RNA genes, 13 protein-coding genes, 22 transfer RNA genes, and one control region (D-loop). Phylogenetic analysis using PAUP based on mitochondrial genome (12 PCGs, except ND6 ) of 16 other Vespertilionidae species revealed the close relationship of M. aurascens with other related Myotis species.